Generic Delimitation between Alstroemeria and Bomarea(Alstroemeriaceae) - Sanso, Andrea Mariel (2001)
The taxonomic relationships between Alstroemeria and Bomarea, two closely related genera in Alstroemeriaceae, are ontroversial. With the aim of clarifying their systematic position and generic circumscription, morphological and anatomical studies were carried out on 18 species of Alstroemeria and 11 species of Bomarea. Light microscopy (LM) and scanning (SEM) and transmission (TEM) electron microscopy were used to study the morphology of mature seeds and pollen. Observations on the most distinctive characters are discussed and compared with other data available for Alstroemeriaceae. Morphology of subterranean organs, pollen exine, adaptive dehiscence of capsules, seed dispersal, seed coat and karyotype characteristics (such as basic chromosome number and symmetry) support the view that these genera are related but should have independent generic status. Results indicate that Alstroemeriaceae comprises three genera: Alstroemeria, (including Schickendantzia and Taltalia), Bomarea and Leontochir.